A state of the art review of solar walls: Concepts and applications. (July 2013) - Saadatian, Omidreza; Lim, Chin Haw; Sopian, Kamaruzzaman; Salleh, Elias
Sustainable energy system design offers credible and innovative strategies to overcome environmental energy crises. Solar walls offer feasible technique for the exploitation of directional flow of heat in buildings. This article reviewed state-of-the-art concepts, applications and significance of solar walls for energy savings in buildings. Detailed operational framework of various solar-wall configurations, technology and efficiency as building component was discussed. Need for this sustainable energy design in buildings and constraints associated with their realisation were reported to aid proposed future research work.